Gene Therapy Restores Mfrp and Corrects Axial Eye Length. Issue 1 (December 2017) - Velez, Gabriel; Tsang, Stephen; Tsai, Yi-Ting; Hsu, Chun-Wei; Gore, Anuradha; Abdelhakim, Aliaa; Mahajan, MaryAnn; Silverman, Ronald; Sparrow, Janet; Bassuk, Alexander; Mahajan, Vinit
Abstract Hyperopia (farsightedness) is a common and significant cause of visual impairment, and extreme hyperopia (nanophthalmos) is a consequence of loss-of-functionMFRP mutations.MFRP deficiency causes abnormal eye growth along the visual axis and significant visual comorbidities, such as angle closure glaucoma, cystic macular edema, and exudative retinal detachment. TheMfrp rd6 /Mfrp rd6 mouse is used as a pre-clinical animal model of retinal degeneration, and we found it was also hyperopic. To test the effect of restoringMfrp expression, we delivered a wild-typeMfrp to the retinal pigmented epithelium (RPE) ofMfrp rd6 /Mfrp rd6 mice via adeno-associated viral (AAV) gene therapy. Phenotypic rescue was evaluated using non-invasive, human clinical testing, including fundus auto-fluorescence, optical coherence tomography, electroretinography, and ultrasound. These analyses showed gene therapy restored retinal function and normalized axial length. Proteomic analysis of RPE tissue revealed rescue of specific proteins associated with eye growth and normal retinal and RPE function. The favorable response to gene therapy inMfrp rd6 /Mfrp rd6 mice suggests hyperopia and associated refractive errors may be amenable to AAV gene therapy.